PENGARUH CITRA, KUALITAS PELAYANAN, DAN KEPUASAN TERHADAP LOYALITAS NASABAH BANK - Julia Hadisurya (Jurnal Manajemen dan Pemasaran Jasa, 2008)
Regarding the growth of banking industry in Indonesia. As we all know, after the economic crisis in 1998 many banks bankrupt and the economic growth after that is not enough significant to return to the bank years in 1990-1995.The objective: How the customer reaction regarding the effort bank to maintain them such as prize, service quality, facility and others.Research design: This research applies non specific bank's customers. The questioner distributed to various places to get various opinion from customers. Data analysis uses in this research was using statistic LISREL 8.7 program. This program tested the customer option toward the hypotheses. The results: Image, services quality and satisfaction give direct impact to the customer loyalty. The bank should carefully take these three factors if they would like to maintain their customer.Keywords: Images, Service Quality, Satisfaction, Loyality.